Houses for a New World Builders and Buyers in American Suburbs, 1945–1965 - Lane, Barbara Miller (Princeton University Press, 2022)
The fascinating history of the twentieth century's most successful experiment in mass housingWhile the work of Frank Lloyd Wright, Richard Neutra, and their contemporaries frequently influences our ideas about house design at the midcentury, most Americans during this period lived in homes built by little-known builders who also served as developers of the communities. Often dismissed as "little boxes, made of ticky-tacky," the tract houses of America's postwar suburbs represent the twentieth century’s most successful experiment in mass housing. Houses for a New World is the first comprehensive history of this uniquely American form of domestic architecture and urbanism.Between 1945 and 1965, more than thirteen million houses—most of them in new ranch and split-level styles—were constructed on large expanses of land outside city centers, providing homes for the country’s rapidly expanding population.